Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.15171/jlms.2017.32
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Level Laser Therapy on Pemphigus Vulgaris Lesions: A Pilot Study

Abstract: Pemphigus vulgaris is a chronic blistering skin disease. Management of recalcitrant pemphigus ulcers is a great problem. Low Level Laser Therapy (LLLT) is known to supply direct biostimulative light energy to body cells. This study evaluates the efficacy of low power laser in the healing of pemphigus lesions. Ten patients with pemphigus vulgaris were enrolled in the trial. The LED-LLLT system used was the Thor LED clusters (109, 69 or 19 diode) (England) with 660 nm wavelength in continuous wave (CW) and 30 mW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(20 reference statements)
1
6
0
1
Order By: Relevance
“…Several studies have reported the benefits of LLLT in oral mucositis and suggested that the combination of infrared and red lasers enhances tissue repair and reduces pain, the need for painkillers, and additional hospital costs 15,16 . Although there are few studies using LLLT as a treatment for PV, some have already reported improvement in the healing of oral lesions and the analgesic effect, so it can be used in addition to drug treatments 9,17,18 . Therefore, we reinforce that LLLT may be used as an adjunct to systemic treatment.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Several studies have reported the benefits of LLLT in oral mucositis and suggested that the combination of infrared and red lasers enhances tissue repair and reduces pain, the need for painkillers, and additional hospital costs 15,16 . Although there are few studies using LLLT as a treatment for PV, some have already reported improvement in the healing of oral lesions and the analgesic effect, so it can be used in addition to drug treatments 9,17,18 . Therefore, we reinforce that LLLT may be used as an adjunct to systemic treatment.…”
Section: Discussionsupporting
confidence: 53%
“…Other advantages of LLLT are immediate analgesia and the quick and non‐invasive nature of the procedure. LLLT has also been proven effective in promoting healing in cases refractory to systemic treatment 9,17 …”
Section: Discussionmentioning
confidence: 99%
“…20 It was verified that, in eight articles of this review, the LPLT action is linked to cellular modulation, that is, the final phase of epithelization. 8,11,13,15,17,34 In these studies, there was an important difference in the remodeling of collagen, with improved scar appearance due to maturation and alignment of the fibers, better underlying skin condition and shorter recovery time, and fewer dehiscences. It is noteworthy that laser was an agent that facilitated the healing of acute injuries, such as that of a patient with surgical wound dehiscence due to Bypass, with complete wound healing and pain improvement after nine applications.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is inferred that although LPLT is a technological possibility that can contribute to the process of tissue regeneration, there are still doubts related to the parameters employed and their actions in the different areas of health care. [6][7][8][9][10][11] • To identify the action of low power laser therapy in the tissue repair of wounds.…”
Section: Integrative Literature Review Articlementioning
confidence: 99%
“…[6][7][8] One of the debated treatment modalities, despite its common use, is low-level laser therapy (LLLT) [9][10][11][12][13][14] that is used in the treatment of many diseases. [15][16][17][18][19][20] Imani et al and Munguia et al concluded that almost 60% of the literature between 2000 to 2018 demonstrated that LLLT was useful in reducing pain and trigger point sensitivity, improving the quality of life. 21,22 Momenzadeh et al 23 reached the same result.…”
Section: Introductionmentioning
confidence: 99%